Patient Satisfaction, Perception-Expectation Gap, and Costumer Satisfaction Index in Annual Survey 2021 at Dr. Soetomo General Academic Hospital - Prakoeswa, Cita Rosita Sigit; Hidayah, Nur; Dewi, Arlina; Purnamasari, Indah; Adriansyah, Agus Aan; Yaqub, Amak M. (Folia Medica Indonesiana, 2022)
Highlights: • Customers expectations at Dr. Soetomo General Academic Hospital has a higher quality of service. • The handling of complaints has a low performance on the quality of services at Dr. Soetomo General Academic Hospital. • Improving service quality requires improvements in efficient complaint handling. Abstract: Service quality is essential in health institutions that can affect patient satisfaction and loyalty. The growth in the number of patients at Dr. Soetomo General Academic Hospital, Surabaya, Indonesia, triggered the diversification of services that require periodic quality control. This study aimed to investigate the performance of 31 departments/units in the hospital, the level of customer satisfaction with services provided, and factors that could influence satisfaction. A survey about service performance, perception, and expectation of services was carried out in 31 departments/units using questionnaires from August to October 2021. Convenient respondents consisted of 2121 patients and their families aged >15. Questionnaire items assessed performance, perceptions, and expectations of health services using the SERVQUAL method. Statistical Package for the Social Sciences (SPSS) software was used to perform an analysis of the results of the measurement and the difference in responses between demographic groups of respondents (p<0.05 was significant). The mean performance score was 92.86, and the gap between their perception and expectation averaged -0.23. Customers' expectations of the provider's competence were met, and its performance was perceived to be the best. Meanwhile, handling complaints was perceived as having the lowest performance, while customers' satisfaction over it had not been met. The results showed that the hospital could still not fully meet some of the customer expectations, with immediate improvements needed in handling complaints.